Promoter hypermethylation of PIWI/piRNA pathway genes associated with diminished pachytene piRNA production in bovine hybrid male sterility - Gong-Wei Zhang; Ling Wang; Huiyou Chen; Jiuqiang Guan; Yuhui Wu; Jianjun Zhao; Zonggang Luo; Wenming Huang; Fuyuan Zuo (Epigenetics, 2020)
Hybrid male sterility (HMS) is a postzygotic reproductive isolation mechanism that enforces speciation. A bovine example of HMS is the yattle (also called dzo), an interspecies hybrid of taurine cattle (Bos taurus) and yak (Bos grunniens). The molecular mechanisms underlying HMS of yattle are not well understood. Epigenetic modifications of DNA methylation and P-element induced wimpy testis (PIWI)-interacting RNA (piRNAs) are important regulators in spermatogenesis. In this study, we investigated DNA methylation patterns and piRNA expression in adult testes in hybrid infertile yattle bulls and fertile cattle and yak bulls using whole genome bisulphite-seq and small RNA-seq. Promoter hypermethylation in yattle were associated with DNA methylation involved in gamete generation, piRNA metabolic processes, spermatogenesis, and spermatid development (P < 2.6 × 10−5). Male infertility in yattle was associated with the promoter hypermethylation-associated silencing of PIWI/piRNA pathway genes including PIWIL1, DDX4, PLD6, MAEL, FKBP6, TDRD1 and TDRD5. The downstream effects of silencing these genes were diminished production of 29- to 31- nucleotide pachytene piRNAs in yattle testes. Hypermethylation events at transposable element loci (LINEs, SINEs, and LTRs) were found in yattle. LINE-derived prepachytene piRNAs increased and SINE-derived prepachytene piRNAs were reduced in yattle testes. Our data suggests that DNA methylation affects the PIWI/piRNA pathway and is involved in gene expression and pachytene piRNA production during spermatogenesis in bovine HMS. DNA hypermethylation and disruption of piRNA production contributed to unsuccessful germ cell development that may drive bovine HMS.